STUDI LITERATUR: EFEKTIVITAS DAN HAMBATAN MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MATEMATIKA PADA SISWA SD - Karina Trisna Putri; Endang M Kurnianti, Susi Winarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of information and communication technology has had a major impact on the world of education, especially at the elementary school level. One of the growing innovations is the use of interactive learning media in supporting the learning process of mathematics. This study aims to examine the effectiveness and obstacles faced in the application of interactive learning media to improve the quality of mathematics learning in elementary school students. The research method used is a literature study by analysing a number of relevant national and international scientific journals published from 2016 to 2025. The results showed that interactive learning media, such as interactive PowerPoint, educational videos, game-based applications, and quiz platforms such as Kahoot, have a positive impact on improving learning outcomes, motivation, and understanding of abstract mathematics concepts. However, in its application, there are still various obstacles, such as limited technological facilities, lack of teacher competence in operating digital media, and limited internet access in some areas. Therefore, collaborative efforts between schools, government, and educators are needed to provide adequate facilities and continuous training to optimise the use of interactive learning media in primary schools.